TINJAUAN TENTANG BUDAYA ISLAM DI TANAH JAWA BERDASARKAN DALIL-DALIL PEMAHAMAN IMAM SYAFIâI - Syarifuddin, Amir; Mustafa, Muhammad Hatta (PARENTAL, 2014)
ABSTRACTThe Islamic tradition which becom the part of islamic life in our Countri, especiallyÂ  inÂ  JavaÂ  island,Â  ratherÂ  hadÂ  shake-up,Â  thisÂ  problemÂ  causedÂ  byÂ  the enternity of the other culture to Indonesia that influence the understanding to each others. The reality insociety shows that islamic tradition which is maintained can limit the negatif effecct of foreign culture which entered, especially western. The reflectionÂ  ofÂ  YasinÂ  andÂ  othersÂ  epistleÂ  inÂ  AlÂ  QurâanÂ  andÂ  tahlil,Â  tasbih,Â  tahmid, shalawat andÂ  other dzikir is a part that can be separated from islamic culture and javaÂ  culture.Â  AllÂ  ofÂ  themÂ  isÂ  reflectedÂ  fromÂ  societyÂ  thatÂ  stillÂ  combineÂ  between cultureÂ  andÂ  religion,Â  itÂ  canÂ  beÂ  understoodÂ  fromÂ  ruwahÂ  culture(ngirim arwah)/ziarah,Â  yassinanÂ  culture,Â  dzikirÂ  culture,Â  andÂ  others.Â  ItÂ  isÂ  canÂ  notÂ  be separatedÂ  fromÂ  islamicÂ  daâwahÂ  thatÂ  spreadÂ  byÂ  waliÂ  songoÂ  thatÂ  acculturatedÂ  the culture, so it is easy to be understood by the society especially Java society.